INFORMATION SYSTEM OF BANK WASTE MANAGEMENT - Tamus Bin Tahir (Patria Artha Technological Journal, 2018)
The purpose of the research is capable of designing a junk bank management information system-based desktop. This research is the kind of research using the method of Research and Development (RnD) and the type of research software engineering using model development. methods of data retrieval for this system is by interview, observation and documentation. The end result of this research is a management information system for desktop-based Junk Bank used the programming language visual basic. The net. Before the application can be used, the validation process is performed by experts. Once validated and get good categories